Antioxidant and Antibacterial Potential of Water Extracts of Selected Plant Species from Tuzla Region (Bosnia and Herzegovina) - Lejla Mekic; Edina Huseinovic; Jasmina Dedic; Darja Husejnagic; Emir Horozic (Biology, Medicine, & Natural Product Chemistry, 2025)
This study aims to determine the antioxidant and antibacterial potential of aqueous extracts of six different plant species, which are widely used in traditional medicine: Salvia officinalis L., Mentha longifolia (L.) Huds., Urtica dioica L., Rosmarinus officinalis L., Rubus fruticosus L. and Achillea millefolium L. The samples were collected in the Tuzla region between March and July 2025. All of the mentioned plants are important in traditional medicine and have been previously reported to have biological activity. The antioxidant activity was tested by the DPPH and FRAP methods, while the antibacterial potential was tested by the diffusion technique on reference bacterial strains from the WDCM collection. The extracts showed high antioxidant activity, with nettle and sage extracts showing the most potent in neutralizing DPPH radicals. Weak to moderate antibacterial activity was recorded in the case of nettle, sage, mint and rosemary extracts, and a complete absence of activity in the case of yarrow and blackberry leaf extracts.